PEMBELAJARAN PENDIDIKAN AGAMA HINDU DALAM BINGKAI KURIKULUM MERDEKA - Dwik, I Made Dwi Susila Adnyana (JAPAM (Jurnal Pendidikan Agama), 2024)
Abstract Learning Hindu Religious Education is a process of knowledge transfer carried out in two ways, namely methodical and logical. Methodical means that Hindu Religious Education learning is carried out using learning methods that are adjusted based on classroom situations and student characteristics; while logical means that learning Hindu Religious Education does not only refer to lectures that are dogmatic, but can also be explained based on logic in accordance with the reality of everyday life. In line with this description, the Merdeka Curriculum plays a role in improving the quality of contemporary Hindu students. The Merdeka Curriculum in principle emphasizes the six dimensions of the Pancasila Student Profile which include: (1) Faith, Fear of God Almighty, and Noble Morals, (2) Global Diversity, (3) Gotong Royong, (4) Independent, (5) Critical Reasoning, and (6) Creative. The role of the Independent Curriculum for Hindu Education is to realize students' śraddhā to be more optimal, have love for others (tat twam asi), and create a directed rationality of students' 'jñāna' so as to create Hindu students who are spiritually and materially intelligent, have a high sense of humanity, are able to solve problems responsibly, and have a creative spirit to be able to compete in the upheaval of the increasingly digital world flower.